2016
DOI: 10.9734/indj/2016/25387
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Substance Use and Psychosocial Competence of Adolescents in Selected Secondary Schools in Uganda: A Cross Sectional Survey

Abstract: Aims1) To determine the nature and extent of alcohol and substance use and 2) To describe the relationship between alcohol use and psychosocial competence among secondary school youths in Northern and Central Uganda.Study DesignThis was a cross-sectional study.Place and Duration of studyDepartments of Mental Health, Gulu University (Northern Uganda) and Department of Psychiatry, Makerere University College of Health Sciences (Central Uganda) between September 2011 and April 2012.MethodologyFour (4) and eight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 35 publications
4
46
1
Order By: Relevance
“…Many Ugandan families have traditionally encouraged their youth to be socially conservative; nevertheless, recent estimates suggest that nearly one-third of Ugandan adolescents had sex1, and two-thirds tried drugs or alcohol during their adolescence2. Depression also has a high burden on Ugandan adolescents, with almost 20% reporting having significant symptoms of depression3.…”
Section: Introductionmentioning
confidence: 99%
“…Many Ugandan families have traditionally encouraged their youth to be socially conservative; nevertheless, recent estimates suggest that nearly one-third of Ugandan adolescents had sex1, and two-thirds tried drugs or alcohol during their adolescence2. Depression also has a high burden on Ugandan adolescents, with almost 20% reporting having significant symptoms of depression3.…”
Section: Introductionmentioning
confidence: 99%
“…In congruence with this finding, Akhter (2013), who studied the relationship between substance use and self-esteem in Pakistan, and reported that low self-esteem was associated with high substance use. In this respect, a study done by Abbo, Okello, Muhwezi, Akello & Ovuga, (2016), asserted that more than two-thirds of substance abusers had low self-esteem. Also, the abovementioned present result was similar to a Turkish study by Zengin & Altay, (2014), which revealed that substance abuse lowers self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, special attention needs to be paid to the consequences of treatment costs and lack of availability of relevant treatment options . Uganda in particular experiences a paucity of treatment services and treatment programs that target adults with individual needs (e.g., Abbo, Okello, Muhwezi, Akello, & Ovuga, 2016).…”
Section: Discussionmentioning
confidence: 99%